Direction- and distance-dependent interareal connectivity of pyramidal cell subpopulations in the rat frontal cortex - Ueta, Yoshifumi; Hirai, Yasuharu; Otsuka, Takeshi; Kawaguchi, Yasuo (Frontiers in Neural Circuits, 2013)
The frontal cortex plays an important role in the initiation and execution of movements via widespread projections to various cortical and subcortical areas. Layer 2/3 (L2/3) pyramidal cells in the frontal cortex send axons mainly to other ipsilateral/contralateral cortical areas. Subpopulations of layer 5 (L5) pyramidal cells that selectively project to the pontine nuclei or to the contralateral cortex (commissural [COM] cells) also target diverse and sometimes overlapping ipsilateral cortical areas. However, little is known about target area-dependent participation in ipsilateral corticocortical (iCC) connections by subclasses of L2/3 and L5 projection neurons. To better understand the functional hierarchy between cortical areas, we compared iCC connectivity between the secondary motor cortex (M2) and adjacent areas, such as the orbitofrontal and primary motor cortices, and distant non-frontal areas, such as the perirhinal and posterior parietal cortices. We particularly assessed the laminar distribution of iCC cells and fibers, and identified the subtypes of pyramidal cells participating in those projections. For connections between M2 and frontal areas, L2/3 and L5 cells in both areas contributed to reciprocal projections, which can be viewed as “bottom-up” or “top-down” on the basis of their differential targeting of cortical lamina. In connections between M2 and non-frontal areas, neurons participating in bottom-up and top-down projections were segregated into the different layers: bottom-up projections arose primarily from L2/3 cells, while top-down projections were dominated by L5 COM cells. These findings suggest that selective participation in iCC connections by pyramidal cell subtypes lead to directional connectivity between M2 and other cortical areas. Based on these findings, we propose a provisional unified framework of interareal hierarchy within the frontal cortex, and discuss the interaction of local circuits with long-range interareal connections.